A relação entre a mídia e a periferia: Um estudo sobre o projeto Central da Periferia da TV Globo - Freitas, Guaciara Barbosa de (Universidade do Vale do Rio dos Sinos, 2011)
This thesis presents the analysis of a set of episodes of Central da Periferia, a TV series displayed by TV Globo from 2006 until 2008. These episodes must be understood based on their productive, televised and socio-cultural dimensions, which are part of the social reality. Therefore, this study gets into the thickness of the socio-cultural mediations in order to characterize aspects of the relation between media and slum. This way, the methodological course establishes a dialogue between the televised narratives constructed in the analyzed episodes and the socio-communicative context voices. A part of the mediatic discourse perform its rhetoric following specificities that are inscribed in consumption social logic, due to this, the media offers us its own meaning of “slum” culture/product. On the other hand, the kind of social organization and mobilization articulated by the groups known as sociocommunicative interferes with the delimitation of the necessary conditions to realize the meaning production process on the slum and its cultural, artistic and communicative outputs. In this process, the slum social actors negotiate with the mediatic system through strategies and tactics that reveal these actors’ ‘art of make’ cultural and communicative products, which differs from the imposed pattern of the commercial and hegemonic media. These negotiation cultural fluxes prove the slum learning force and communicative know-how, what seemed to be restricted to the mediatic communication area, and now points to the beginning of a powering process, that is able to arouse meaningful displacements in the power system structure.
Keywords: Movimentos sociocomunicacionais; Central da Periferia; Periferia; Mídia; Socialcommuncations movements; Slum; Media; ACCNPQ::Ciências Sociais Aplicadas::Comunicação